Circulating tumor-associated biomarkers and pulmonary function in lung cancer patients with comorbid COPD: A retrospective prognostic analysis: Biochemical prognostic markers in lung cancer with COPD - Ma, Hongxia; Zhang, Qian; Yue, Junnan; Su, Jun; Meng, Xingrui; Ren, Fangyuan; Li, Zheng (Journal of Medical Biochemistry, 2026)
Background: Chronic obstructive pulmonary disease (COPD) is closely associated with lung cancer development and progression through persistent systemic inflammation and immune-biochemical alterations. Circulating tumor-associated biochemical biomarkers may reflect disease severity and provide valuable prognostic information. This study aimed to explore the potential association between circulating tumor markers and prognosis in lung cancer patients with comorbid COPD, acknowledging the exploratory nature of this retrospective analysis. Methods: Clinicopathological characteristics and circulating biochemical biomarkers, including carcinoembryonic antigen (CEA), carbohydrate antigen 125 (CA125), carbohydrate antigen 153 (CA153), carbohydrate antigen 199 (CA199), cytokeratin-19 fragment (CYFRA21-1), and vascular endothelial growth factor (VEGF), were analyzed. Multivariate logistic regression was performed to identify independent prognostic biochemical predictors. Receiver operating characteristic (ROC) curve analysis was used to evaluate prognostic performance. Results: Patients with COPD demonstrated significantly elevated circulating levels of tumor-associated biochemical biomarkers compared with those without COPD (P<0.05). Multivariate analysis identified advanced TNM stage, lymph node metastasis, and increased serum concentrations of CYFRA21-1, CEA, CA125, CA153, CA199, and VEGF as independent biochemical predictors of poor prognosis (P<0.05). ROC curve analysis showed that CA199 (AUC>0.75), CA153 (AUC>0.75), and CA125 (AUC>0.75) exhibited strong prognostic performance, indicating their clinical utility for laboratory-based risk stratification. Conclusions: In this retrospective analysis, circulating tumor-associated biochemical biomarkers showed potential associations with prognosis in lung cancer patients with COPD. However, these findings are hypothesis-generating and require prospective validation before clinical implementation. The observed associations should not be interpreted as established prognostic markers for clinical decision-making without further multi-center, prospective studies. Current evidence supports continued reliance on established staging systems and comprehensive clinical assessment rather than biomarker-based risk stratification alone.